The philosophical writings of Descartes - Descartes, René, 1596-1650; Cottingham, John, 1943-; Stoothoff, Robert; Murdoch, Dugald, 1944- (Cambridge : Cambridge University Press, 1984)
These two volumes provide a translation of the philosophical works of Descartes, based on the best available Latin and French texts. They are intended to replace the only reasonably comprehensive selection of his works in English, by Haldane and Ross, first published in 1911. All the works included in that edition are translated here, together with a number of additional texts crucial for an understanding of Cartesian philosophy, including important material from Descartes' scientific writings. The result should meet the widespread demand for an accurate and authoritative edition of Descartes' philosophical writings in clear and readable modern English.
v. 3 Introduction--Chronological Table--Table of Letters Translated--Letters--Notes on Descartes' Correspondents--Table of Citations of Descartes' works--Index.
Title from publisher's bibliographic system (viewed on 18 Jul 2016).
Keywords: elektronické knihy; electronic books; Descartes, René, -- 1596-1650.; Philosophy